GENERATOR PROTECTION STUDIES AT KAPAR ENERGY VENTURES POWER STATION (KEV) - SULAIMAN, MASHITAH (Universiti Teknologi Petronas, 2009)
The main purpose of electric device is to isolate the faulted component from the healthy part as fast as possible in order to prevent further damage and endangering human life. The objectives of these studies are to study the overall generator and generator transformer protection at Kapar Energy Ventures and propose recommendation to improve the protection setting and coordination (if required).Generator protection is very important to safe guard the generator at Kapar Energy Ventures power station. Nevertheless, the auxiliary system to the generator plays an equally vital role to ensure that the generator continue to work as intended. There were times that generator and its auxiliary equipment had tripped due to miscoordinated protection system or wrong settings. A protection system must satisfy the following requirements Selective - disconnect the equipment is restricted to the nurumum necessary to isolate fault. Sensitivity - sensitive enough to operate under minimum fault condition. Stable - stable and remain inoperative under certain specific condition . Fast - fast operation in order to clear the fault from the system and to minimize damage to the affected component Reliable - the protective equipment should not fail to operate in the events of faults in the protected zone. It may be necessary to provide backup protection to cover the failure the remaining protection